The basic requirements for tax reporting by budget institutions - Карпенко, Н. Г. (Scientific Progress & Innovations, 2016)
The procedure of preparation and presentation of the tax reporting by budget institutions, the organizational stages of formation of the tax reporting are studied in the article. The sources of information for determination of the amount of payments, fees and preparation of tax reporting are outlined in the article. We identify important information on mandatory of tax reporting and details of filling in the reporting forms. According to the research results the attention is focused on the responsibility of officials for timely payment of paying and taxes, formation and presentation of reporting of budgetary institutions.